2022
DOI: 10.3390/jof8101021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacillus velezensis SBB and Its Antifungal Effects against Verticillium dahliae

Abstract: Traditional control methods have drawbacks in controlling Verticillium wilt diseases caused by Verticillium dahliae Kleb.; therefore, an efficient and environmentally friendly strategy for disease control must be identified and the mechanisms determined. In this study, a soil-isolated strain SBB was identified as Bacillus velezensis based on 16S rRNA, gyrA, and gyrB gene sequences. In vitro, strain SBB had excellent inhibitory effects on V. dahliae, with the highest inhibition rate of 70.94%. Moreover, strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…T6 [ 64 ]. B. velezensis SBB VOCs (2-nonanol—0.06 μL/mL, 2-heptanone—0.3 μL/mL, 6-methyl-2-heptanone—0.3 μL/mL, and 2-nonanone—0.6 μL/mL) completely inhibited Verticillium dahliae growth in vitro and inhibited production of conidia and microsclerotia [ 80 ]. Phenylacetic acid and methylphenyl acetate produced by B. mycoides BM02 suppressed spore germination but had no effects on the hyphal growth of Fusarium oxysporum f. sp.…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
See 1 more Smart Citation
“…T6 [ 64 ]. B. velezensis SBB VOCs (2-nonanol—0.06 μL/mL, 2-heptanone—0.3 μL/mL, 6-methyl-2-heptanone—0.3 μL/mL, and 2-nonanone—0.6 μL/mL) completely inhibited Verticillium dahliae growth in vitro and inhibited production of conidia and microsclerotia [ 80 ]. Phenylacetic acid and methylphenyl acetate produced by B. mycoides BM02 suppressed spore germination but had no effects on the hyphal growth of Fusarium oxysporum f. sp.…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…lactucae [ 1 ]. B. velezensis SBB VOCs (2-nonanol, 2-heptanone, 6-methyl-2-heptanone, and 2-nonanone) inhibited melanin production by Verticillium dahliae [ 80 ]. Melanin plays an important role in providing the mechanical strength required for germ tubes, obtained by conidia germination, to penetrate host tissues [ 93 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…The major gene clusters identified in the bacterial genomes include macrolactin, bacillaene, bacilysin, bacillibactin, fengycin, and iturin A ( Table 3 ; Figure 6 ). Biosynthesis and secretion of these compounds by Bacillus isolates have been shown direct mechanisms to suppress plant pathogens ( Bidima et al, 2022 ; Wang et al, 2022 ). Several studies reported that the macrolide compounds such as macrolactin, bacillaene, and difficidin inhibit protein synthesis, impair cell division, and damage the cell membrane to restrict the growth of phytopathogens ( Wu et al, 2015 ; Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies suggest that these compounds also play a role in transcription regulation and enhance plant resistance against phytopathogens ( Chen et al, 2021 ; Surovy and Islam, 2021 ). Siderophores such as bacilibactin and bacilysin suppress fungal growth by competing for nutrition ( Dimopoulou et al, 2021 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis and secretion of all these compounds by Bacillus spp. have shown direct mechanisms to suppress plant pathogens [57,58,59]. Several studies reported that the macrolide compounds macrolactin, bacillaene, and difficidin inhibit protein synthesis, impair cell division, and damage the cell membrane to restrict growth of phytopathogens [33,60].…”
Section: Discussionmentioning
confidence: 99%